2021
DOI: 10.1093/humrep/deab260
|View full text |Cite
|
Sign up to set email alerts
|

Striving for motherhood after uterus transplantation: a qualitative study concerning pregnancy attempts, and the first years of parenthood after transplantation

Abstract: STUDY QUESTION How do women experience attempts to become pregnant, and the first years of motherhood, after uterus transplantation (UTx)? SUMMARY ANSWER Women who try to become pregnant after UTx experience the general strains typically associated with infertility and childlessness, such as failure of embryo transfer (ET), and specific worries about graft survival but when they become mothers they essentially feel like other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It was concluded that the self-image was in general positively affected. The other study explored experiences of attempting pregnancy and of motherhood, identifying an overarching theme of ‘experiencing the previously unimaginable’, with underlying subthemes of ‘the yoke of childnessness’, ‘going through the impossible’, and ‘motherhood as surreal and normal’ ( Järvholm et al , 2022 ). It was summarized that women with UTx experience the common worry about implantation failure at ET, specific worries of graft failure and, when they become mothers, they feel like other mothers, with the associated stresses and rewards.…”
Section: Long-term Health Outcome After Uterus Transplantationmentioning
confidence: 99%
“…It was concluded that the self-image was in general positively affected. The other study explored experiences of attempting pregnancy and of motherhood, identifying an overarching theme of ‘experiencing the previously unimaginable’, with underlying subthemes of ‘the yoke of childnessness’, ‘going through the impossible’, and ‘motherhood as surreal and normal’ ( Järvholm et al , 2022 ). It was summarized that women with UTx experience the common worry about implantation failure at ET, specific worries of graft failure and, when they become mothers, they feel like other mothers, with the associated stresses and rewards.…”
Section: Long-term Health Outcome After Uterus Transplantationmentioning
confidence: 99%
“…Most women with MRKHs later in life are almost comparable to the general population regarding QOL [52], but questions regarding fertility and sexual self-esteem are reported to be negatively affected [53]. UTx is mainly experienced as a road to motherhood [34 ▪▪ ], but the time with the uterus also provides a change in self-perception when having the bodily changes like everyone else [17 ▪▪ ,18 ▪▪ ]. Follow-up with standardized questionnaires have, so far, shown that the group of women who have undergone the procedure are fairly stable [42 ▪ ,43].…”
Section: Outcomes Of Vascularized Composite Allotransplantationmentioning
confidence: 99%
“…Another important difference between the UTx and other VCA procedures is the temporary adjustment to the graft as the graft will be removed after achieving its purpose, delivery of children. The removal of the uterus, if it has to be successful, can result in an experience of ‘being back to me’ [34 ▪▪ ] or a negative impact on self-esteem [18 ▪▪ ]. The exit strategies must be discussed at several time-points both with those who become parents as well with those with graft-failure.…”
Section: Adherence and Rehabilitation Are A Life(graft-)-time Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Declines were reported and may have been associated both with unsuccessful outcomes of the graft as well with general life changes, such as retirement ( Järvholm et al , 2019 ). Qualitative follow-up studies showed that the state of having a uterus affected the recipient’s self-image in a positive way, but this was also associated with strains regarding body image and sexuality, and after giving birth the recipients saw themselves as almost like everyone else but with a special experience in their road to motherhood ( Järvholm et al , 2020 , 2022 ). From a large UTx centre in USA, a 2-year follow-up study with qualitative data of recipients reported positive impacts regarding their reproductive autonomy and female identity ( Wall et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%